2016
DOI: 10.18632/oncotarget.11871
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of the IHH gene into rabbit BMSCs in a simulated microgravity environment promotes chondrogenic differentiation and inhibits cartilage aging

Abstract: The effect of overexpressing the Indian hedgehog (IHH) gene on the chondrogenic differentiation of rabbit bone marrow-derived mesenchymal stem cells (BMSCs) was investigated in a simulated microgravity environment. An adenovirus plasmid encoding the rabbit IHH gene was constructed in vitro and transfected into rabbit BMSCs. Two large groups were used: conventional cell culture and induction model group and simulated microgravity environment group. Each large group was further divided into blank control group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The device contained four parts: cell culture units, liquid storage units, an automatic liquid change system, and an electronic control system. 60 The cell observation units used on the Tianzhou-1 cargo ship, in which 60-80 Cytodex 3 microcarriers 64,65 laden with attached HPCs (over 80% of the microcarriers were covered with cells, 5-20 cells per ball) were exposed to 1.8 ml of medium, were separated by two pieces of polycarbonate filter membrane at each end to prevent pollution from the liquid storage units (Fig. 1b).…”
Section: Methodsmentioning
confidence: 99%
“…The device contained four parts: cell culture units, liquid storage units, an automatic liquid change system, and an electronic control system. 60 The cell observation units used on the Tianzhou-1 cargo ship, in which 60-80 Cytodex 3 microcarriers 64,65 laden with attached HPCs (over 80% of the microcarriers were covered with cells, 5-20 cells per ball) were exposed to 1.8 ml of medium, were separated by two pieces of polycarbonate filter membrane at each end to prevent pollution from the liquid storage units (Fig. 1b).…”
Section: Methodsmentioning
confidence: 99%
“…MSCs cultured in two-dimensional (2D) conventional tissue culture polystyrene flasks can result in extremely low yields, which can limit its clinical application. In our previous study, we have demonstrated that MSCs can promote the generation of cartilage and inhibit cartilage aging and osteogenesis when cultures in a 3D microgravity environment (Liu et al 2016). We hypothesized that 3D culture might be an important factor for improved biological function.…”
Section: Introductionmentioning
confidence: 98%
“…11,[45][46][47] In a previous study, concomitant transfection of hMSCs in pellet culture with IHH and TGF-b1 increased the expression of hypertrophic markers ALP and Col X as well as GAG content, 48 which was consistent with our results in Figure 6. In other studies, rabbit MSCs overexpressing IHH had higher expression of hypertrophic markers ALP and Col X compared with the untreated MSCs after 21-day incubation in chondrogenic medium, 49 and chondrocytes overexpressing IHH, isolated from the middle zone of articular cartilage, underwent hypertrophy and differentiated into the calcified zone chondrocytes. 9,50 Several studies suggest that the superficial zone chondrocytes have the capacity to differentiate and mature to the middle and calcified zone chondrocytes.…”
Section: Discussionmentioning
confidence: 80%